(untitled) (Indian Journal of Chemistry (IJC), 2023)
The target molecule 2,6-bis(4-hydroxy-3-methoxyphenyl)-3,5-dimethylpiperidin-4-one (BHMD) has best binding energy of –7.5 kcal/mol with 5YOK protein of HIV-1 protease. The theoretical studies of the target molecule have been carried out using Gaussian 16W software and viewed by Gaussview 06 software. Bond length, bond angle and dihedral angle of optimized geometry have been performed by DFT method with B3LYP/6-311G (d,p) basis set. The charge transfer and electronic properties of the target molecule have been explained on the basis of highest occupied molecular orbital and lowest unoccupied molecular orbital and its energy values have been used for calculating the global chemical reactivity parameters. In addition to that, molecular electrostatic potential and Mulliken population analysis have been calculated and discussed for predicting the reactive site. NBO analysis has been used to study the charge delocalization and stability of the molecule. NCI and shaded surface map with projection effect of electron localization function have also been studied by Multiwfn 3.8 software.